PENYULUHAN TENTANG PENTINGNYA PEMBERIAN ASI EKSKLUSIF DAN IMUNISASI DASAR LENGKAP PADA BAYI DI DESA PAKONG KABUPATEN PAMEKASAN - Emi Yunita; Layla Imroatu Zulaikha (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
The direct causes of nutritional problems are infectious diseases and lack of balanced nutrition. Incomplete basic immunization and not getting exclusive breastfeeding are factors for infection. Immunization plays an important role in the formation of a toddler's immune system, children who get complete immunization have a stronger immune system, breastfeeding for less than 6 months is more at risk than toddlers who are breastfed for 6 months against infections and malnutrition, loss of body minerals, and slow growth. lead to malnutrition and stunting in children. The strategy to improve the nutritional status of the community and overcome nutritional problems to reduce infant and under-five mortality rates continues to be mobilized. Immunization is an important program in order to accelerate the improvement of health status, because infectious diseases are the cause of malnutrition and even child mortality. The target for complete basic immunization coverage and coverage has not been achieved. Exclusive breastfeeding causes the prevalence of nutritional problems for children under five in Indonesia is still high, the results of research are still controversial about the relationship between immunization and exclusive breastfeeding with nutritional status. The problem of stunting is one of the